Identifikasi Sifat Elektrolit Buah-buahan Impor melalui Uji Elektrolisis - Iis Siti Jahro; Rafli Hutauruk; Jansen Riko Perangin Angin; Mutiara Evelin Yoseva Marpaung; Sheila Sakinah; Hotman Priwaldi Sijabat; Arina Sami Sarah; Mutiah Khaira (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to identify the electrolyte properties of various imported fruits through electrolysis experiments. A quantitative approach was used by measuring the presence of gas bubbles formed on electrodes as an indicator of electrolyte strength. Samples included apples, pears, grapes, lemons, mandarins, strawberries, cherries, kiwis, blueberries, and dates. The results showed that all tested fruit extracts exhibited electrolyte properties due to the presence of organic acids (such as citric, malic, and tartaric acids) and minerals that can ionize into free ions. Apples showed the strongest electrolyte activity, followed by pears, grapes, lemons, and mandarins, while cherries, kiwis, blueberries, and dates showed weaker conductivity. Electrolyte strength was influenced by factors such as ion concentration, acid type, and mineral content. These findings suggest that fruit extracts, especially those with higher acidity levels, have the potential to act as natural electrolytes and serve as an alternative source of environmentally friendly electrical energy.